(untitled) (Clinics, 2012)
OBJECTIVE: Endostatin is a potent endogenous inhibitor of angiogenesis. It is derived from the proteolytic cleavage of collagen XVIII, which is encoded by the COL18A1 gene. A polymorphic COL18A1 allele encoding the functional polymorphism p.D104N impairs the activity of endostatin, resulting in a decreased ability to inhibit angiogenesis. This polymorphism has been previously analyzed in many types of cancer and has been considered a phenotype modulator in some benign and malignant tumors. However, these data are controversial, and different results have been reported for the same tumor types, such as prostate and breast cancer. The purpose of this study was to genotype the p.D104N variant in a cohort of pediatric and adult patients with adrenocortical tumors and to determine its possible association with the biological behavior of adrenocortical tumors. METHODS: DNA samples were obtained from 38 pediatric and 56 adult patients (0.6-75 yrs) with adrenocortical tumors. The DNA samples were obtained from peripheral blood, frozen tissue or paraffin-embedded tumor blocks when blood samples or fresh frozen tissue samples were unavailable. Restriction fragment length polymorphism analysis was used to genotype the patients and 150 controls. The potential associations of the p.D104N polymorphism with clinical and histopathological features and oncologic outcome (age of onset, tumor size, malignant tumor behavior, and clinical syndrome) were analyzed. RESULTS: Both the patient group and the control group were in Hardy-Weinberg equilibrium. The frequencies of the p.D104N polymorphism in the patient group were 81.9% (DD), 15.9% (DN) and 2.2% (NN). In the controls, these frequencies were 80.6%, 17.3% and 2.0%, respectively. We did not observe any association of this variant with clinical or histopathological features or oncologic outcome in our cohort of pediatric and adult patients with adrenocortical tumors.